Growth and variability of rice in Raisen district of Madhya Pradesh - Raghuwanshi, Ram Swarup; Prusty, Suvashree R; Raghuwanshi, Naval Kishor (ORYZA-An International Journal of Rice, 2018)
The present study was undertaken in Raisen district of Madhya Pradesh using the secondary collected data of area, production and productivity to estimate the variability in area, production and productivity, to find out the trend and growth rates of area production and productivity and to identify the major factors affecting the production and productivity of rice. Coefficient of variation was used to find out the variability in growth rate and least square method for the trend analysis and fitting the linear model. It was found that high variability in production of rice was mainly due to variability in area and productivity in the study area. The growth in area of paddy has positive and significant impact on production and productivity in all the tehsils except Udaipura. Near about 89 per cent of variation of yield of paddy was contributed by all four variables like net irrigated area, gross irrigated area, irrigated area of rice and irrigated area of HYV rice in the study area.